Microenvironment engineering by targeted delivery of Ag nanoparticles for boosting electrocatalytic CO2 reduction reaction - Ting Xu; Hao Yang; Tianrui Lu; Rui Zhong; Jing-Jing Lv; Shaojun Zhu; Mingming Zhang; Zheng-Jun Wang; Yifei Yuan; Jun Li; Jichang Wang; Huile Jin; et al. (Nature Communications)
Abstract Creating and maintaining a favorable microenvironment for electrocatalytic CO2 reduction reaction (eCO2RR) is challenging due to the vigorous interactions with both gas and electrolyte solution during the electrocatalysis. Herein, to boost the performance of eCO2RR, a unique synthetic method that deploys the in situ reduction of precoated precursors is developed to produce activated Ag nanoparticles (NPs) within the gas diffusion layer (GDL), where the thus-obtained Ag NPs-Skeleton can block direct contact between the active Ag sites and electrolyte. Specifically, compared to the conventional surface loading mode in the acidic media, our freestanding and binder free electrode can achieve obvious higher CO selectivity of 94%, CO production rate of 23.3 mol g−1 h−1, single-pass CO2 conversion of 58.6%, and enhanced long-term stability of 8 hours. Our study shows that delivering catalysts within the GDL does not only gain the desired physical protection from GDL skeleton to achieve a superior local microenvironment for more efficient pH-universal eCO2RR, but also manifests the pore structures to effectively address gas accumulation and flood issues.